Concomitant and Bismuth Quadruple Therapy for Helicobacter pylori Eradication in Southern Italy: Preliminary Data from a Randomized Clinical Trial - Giuseppe Losurdo; Antonia Valeria Borraccino; Adriana Aloisio; Francesco Russo; Giuseppe Riezzo; Grazia Galeano; Maria Pricci; Bruna Girardi; Francesca Celiberto; Andrea Iannone; Enzo Ierardi; Alfredo Di Leo (MDPI AG, 2024)
Concomitant therapy (CT) and bismuth quadruple therapy (BQT) are recommended in geographical areas with high clarithromycin resistance for Helicobacter pylori (H. pylori) eradication. We compared CT and BQT as the first lines of treatment in a randomized controlled trial. Consecutive patients with H. pylori diagnosed by concordance of both a urea breath test and histology were recruited. For BQT, patients received 3 PyleraTM capsules q.i.d.; for CT, 1000 mg of amoxicillin b.i.d, 500 mg of clarithromycin b.i.d and 500 mg of metronidazole b.i.d. As a proton pump inhibitor, 40 mg of pantoprazole b.i.d was administered. Both regimens lasted 10 days. In total, 46 patients received CT and 38 BQT. Both groups were comparable for age (p = 0.27) and sex (p = 0.36). We did not record any drop outs; therefore, the intention to treat and per protocol rates coincided. The most common symptoms were heartburn and post-prandial fullness, which were equally present in both groups. The success rate was 95.6% for CT and 100% for BQT (p = 0.56). Side effects were recorded in 23.9% and 31.6% of patients in the CT and BQT arms, respectively (p = 0.47). The most common ones were abdominal pain (8) and diarrhea (6). In conclusion, CT and BQT are equally effective in our area with high clarithromycin resistance, southern Italy, and showed comparable safety.